2006
DOI: 10.1080/00268970500285029
|View full text |Cite
|
Sign up to set email alerts
|

Quasiresonance

Abstract: The concept of quasiresonance was introduced in connection with inelastic collisions between one atom and a vibro-rotationally excited diatomic molecule. In its original form, the collisions induce quasiresonant transfer of energy between the internal degrees of freedom of the diatom: there is a surprisingly accurate low order rational value for the ratio of the changes in the vibrational and rotational classical actions, provided the vibrational and rotational frequencies of the diatom are approximately relat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 15 publications
(45 reference statements)
1
19
0
Order By: Relevance
“…This effect was experimentally observed for certain regions of initial internal molecular states, provided that the collision time was longer that the molecular period. Similar results were reproduced in classical trajectory studies of the collision process [2,3,4].Recently the concept of quasiresonance has been extended to new processes in different systems [5,6]. It has been shown that this is a common effect which arises from the perturbative transient interaction between quasiresonant, i.e.…”
supporting
confidence: 68%
See 3 more Smart Citations
“…This effect was experimentally observed for certain regions of initial internal molecular states, provided that the collision time was longer that the molecular period. Similar results were reproduced in classical trajectory studies of the collision process [2,3,4].Recently the concept of quasiresonance has been extended to new processes in different systems [5,6]. It has been shown that this is a common effect which arises from the perturbative transient interaction between quasiresonant, i.e.…”
supporting
confidence: 68%
“…Recently the concept of quasiresonance has been extended to new processes in different systems [5,6]. It has been shown that this is a common effect which arises from the perturbative transient interaction between quasiresonant, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, the internal energy transfer can be unusually efficient and specific. Such cases are often referred to as "quasiresonant" [8]. For example, quasiresonant vibration-rotation (QRVR) energy transfer occurs in atom-diatom collisions when the ratio of the rotational and vibrational periods of the diatom is nearly equal to an integer.…”
mentioning
confidence: 99%